2021
DOI: 10.1101/2021.09.27.461948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammasome activation in infected macrophages drives COVID-19 pathology

Abstract: Chronic COVID-19 is characterized by persistent viral RNA and sustained interferon (IFN) response which is recapitulated and required for pathology in SARS-CoV-2 infected MISTRG6-hACE2 humanized mice. As in the human disease, monocytes, and macrophages in SARS-CoV-2 infected MISTRG6-hACE2 are central to disease pathology. Here, we describe SARS-CoV-2 uptake in tissue resident human macrophages that is enhanced by virus specific antibodies. SARS-CoV-2 replicates in these human macrophages as evidenced by detect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Our scRNA-seq and smFISH analyses indicate that SARS-CoV-2 can also infect alveolar macrophages, as previously surmised 21,23 . However, in contrast to activated interstitial macrophages, there is neither viral takeover of the host cell transcriptome nor cell-autonomous induction of a substantial inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our scRNA-seq and smFISH analyses indicate that SARS-CoV-2 can also infect alveolar macrophages, as previously surmised 21,23 . However, in contrast to activated interstitial macrophages, there is neither viral takeover of the host cell transcriptome nor cell-autonomous induction of a substantial inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
“…This could be due to effective host control or destruction of the virus in alveolar macrophages, or to viral evasion of detection 61 in order to complete its replication cycle (see accompanying manuscript). As other studies have also identified the importance of macrophage infection to COVID-19 pathogenesis 2123 , our results highlight the need in future COVID-19 studies to resolve the molecular subtype of lung macrophages infected, the extent of their viral takeover, and the specific host cell response, in evaluating the role of infected macrophages in the disease.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Afucosylated IgG1 may support antigen presentation on antigen-presenting cells through FcγRIIIa, as well as inducing better T-helper and memory B cell responses, and subsequent booster responses (43)(44)(45). In support of this, we observed that early afucosylated anti-S IgG1 responses correlated significantly with anti-S IgG levels after the second dose in naive individuals (41).…”
Section: Discussionmentioning
confidence: 99%